The interaction of cognition and language: a psycholinguistic perspective on language processing and acquisition - Sobirova , Feruza (The Lingua Spectrum, 2025)
Psycholinguistics combines psychology and linguistics to study language acquisition, comprehension, and production. This interdisciplinary field integrates cognitive psychology, neurology, and computational modelling to study the mechanisms that underpin language processing. This article investigates how essential cognitive skills such as working memory, attention, and brain activation contribute to language acquisition and understanding. Furthermore, it investigates bilingualism’s impact on cognitive flexibility, the significance of psycholinguistic models in diagnosing and treating language disorders, and new breakthroughs in neurolinguistic research. The debate includes applied psycholinguistics, including language teaching, artificial intelligence, and therapeutic rehabilitation. This work gives a thorough explanation of the interaction between language and cognition by combining theoretical ideas with experimental findings, contributing to both theoretical advances and practical applications in psycholinguistics.